Afro-caririense cultural heritage: ancestral technology of potengi blacksmiths - dos Santos, Ana Paula (2020)
Bearing in mind the academic productions about the Cariri region, with a bias crossed by the Afro-descendant approach, which does not lose sight of the diverse possibilities of existence of the black population in the formation of the territory, this article aims to problematize Cariri's Africanities from work centenary of blacksmiths in the city of Potengi, south of the state of Ceará. For this, a specific reference was used on the importance of iron for African culture, understanding it as a very old technology, transported and reframed in Afro-Cariri culture. The field study as a methodology, in an ethnic perspective, was necessary for us to know the local dynamics that surround this ancient knowledge. As a result, this writing, as well as the work carried out by the blacksmiths, is a didactic-pedagogical possibility for teaching the culture, history, chemistry and technology of the local territory.